Magnetic and electric responsive hydrogel-magnetic nanocomposites for drug-delivery application - Reddy, N. Narayana; Mohan, Y. Murali; Varaprasad, K.; Ravindra, S.; Joy, Pattayil Alias; Raju, K. Mohana (Journal of Applied Polymer Science, 2011)
Magnetic and electrically responsive hydrogel networks were developed for drug-delivery applications. The hydrogel matrices were synthesized by the polymerization of acrylamide monomer in the presence of carboxymethylcellulose (CMC) or methylcellulose (MC) with N,N-methylenebisacrylamide, a crosslinker with the redox initiating system ammonium persulfate/tetramethylethylenediamine. The magnetic nanoparticles were generated throughout these hydrogel matrices by an in situ method by the incorporation of iron ions and their subsequent reduction with ammonia. A series of hydrogel-magnetic nanocomposites (HGMNCs) were developed with various CMC and MC compositions. The synthesized HGMNCs were characterized with spectral (Fourier transform infrared and ultraviolet-visible spectroscopy), X-ray diffraction, thermal, and microscopy methods. These HGMNCs contained iron oxide (Fe3O4) nanoparticles with an average particle size of about 22 nm, as observed by transmission electron microscopy. The dielectrical properties of the pure hydrogel (HG); the hydrogel loaded with iron ions, or the hydrogel iron-ion composite (HGIC); and the HGMNCs were measured. These results suggest that HGMNCs exhibited higher dielectric constants compared to HG and HGICs. The curcumin loading and release characteristics were also measured for HG, HGIC, and HGMNC systems. These data revealed that there was a sustained release of curcumin from HGMNCs because of the presence of magnetic nanoparticles in the hydrogel networks. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1364-1375, 2011
Keywords: hydrogels; magnetic polymers; Nanocomposites; nanoparticle; nanotechnology

Reactive polymers bearing styrene pendants through selective anionic polymerization of 4-vinylbenzyl methacrylate - Mohan, Y. Murali; Raghunadh, V.; Sivaram, S.; Baskaran, D. (Macromolecules, 2012)
Selective anionic polymerization of 4-vinylbenzyl methacrylate at methacrylate site has been achieved using resonance stabilized anionic initiators such as 1,1-diphenylhexyllithium (DPHLi) and tritylpotassium (TritylK) in tetrahydrofuran (THF) at -78 degrees C. Polymerization proceeded selectively through methacrylate functionality of the monomer in a controlled manner and produced polymers and copolymers with narrow molecular weight distribution at low temperatures (<=-40 degrees C). H-1 NMR of the polymer showed the presence of styrene pendants in every monomeric repeating unit. The polymerization results confirm that the resonance stabilized carbanions with an optimum pK(a) (30 <= pK(a) <= 32) of their conjugate acids such as DPHLi and TritylK do not react with styrene functionality at 78 degrees C. The selective initiation without cross-linking is attributed to the differences in the electronegativity between polar methacrylate and styrene functionalities and an attenuation of initiator reactivity at low temperature. Poly(4-vinylbenzyl methacrylate) and its copolymers with the vinyl pendant in close proximity with ester linkage are very reactive and unstable, readily undergoing cross-linking in solution or in solid state with or without a radical initiator.